Protein Adsorption on Hybrids of Thermoresponsive Polymers and Single-Walled Carbon Nanotubes - Kazuo Umemura; Katsuki Izumi; Yoshikazu Kumashiro; Shusuke Oura; Teruo Okano (International Journal of Polymer Science)
Poly(N-isopropylacrylamide) (PNIPAAm) is one of the most popular thermoresponsive polymers. Adsorption of RecA proteins onto hybrids of PNIPAAm and single-walled carbon nanotubes (SWNTs) was observed in the presence and absence of DNA molecules. Although RecA molecules were adsorbed efficiently onto the hybrid surfaces at 37°C, even in the absence of DNA molecules, the adsorption of RecA was inhibited at 4°C. These results suggest that the thermoresponsive functions of PNIPAAm were effective, even on the SWNT surfaces, which supports the possibility of developing nanobiodevices using PNIPAAm-SWNT hybrids. However, although RecA is a DNA binding protein, there was no significant difference in the adsorption of RecA onto PNIPAAm-SWNT surfaces with and without DNA molecules. This study provides fundamental information for potential biological applications of PNIPAAm-SWNT hybrids.